Home parenteral nutrition in patients receiving palliative care: a curriculum-based review. Issue 4 (17th December 2018) - Fletcher, Jane; Woodham, Diane; Dera, Merceline; Cooper, Sheldon C
Abstract : Difficulty with maintaining nutritional intake is common in patients with cancer. European guidance suggests that wherever possible nutritional support should first be provided by the oral or enteral route. Where this is not possible, for example, in malignant small bowel obstruction, parenteral nutrition (PN) may be considered. In palliative care, it is generally accepted that the significant risks and burdens of PN outweigh the potential benefits in patients with an expected survival <2 months. Determining prognosis is crucial when helping patients to make decisions regarding appropriate care pathways; however, this remains challenging. An overview of clinical issues and prognostic indicators related to selecting patients appropriately for palliative PN is given to cover the relevant advanced competencies of the 2010 Gastroenterology Curriculum. The organisation of Home Parenteral Nutrition (HPN) services in England is described including the associated risks and burdens of HPN in the palliative patient.